Mathematical Language Errors and Academic Performance in Preservice Calculus Teachers - Baidoo, Joseph (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2025)
This study explores the impact of mathematical language errors (MLE) on the academic achievement of preservice calculus teachers, addressing the critical issue of how these errors impede mathematical understanding and performance. Conducted within the context of South Africa's education system, where effective mathematics instruction is vital for educational and economic development, this study aims to identify common mathematical language pitfalls, analyze their consequences, and propose strategies to mitigate these errors. An exploratory sequential mixed-methods design was employed, combining qualitative and quantitative approaches to understand the issue comprehensively. The study involved 120 preservice teachers divided into first and second-year cohorts. Data collection included qualitative analysis of student responses through thematic coding and quantitative analysis of assessment results using descriptive statistics, chi-square test, and ANOVA. Significant findings identified two major MLE types: incorrect terminology and ambiguous language errors, which were prevalent and significantly impacted academic performance. First-year students exhibited higher frequencies of these errors, correlating with lower academic scores than second-year students. Statistical analyses confirmed significant differences in error distribution and their impact on performance, highlighting the need for early and targeted interventions. The study contributes to the literature on mathematics education by highlighting the importance of mathematical language in education and provides evidence-based strategies for improving mathematical instruction. By addressing mathematical language errors through explicit instruction, interactive activities, and peer feedback, mathematics educators can enhance students' understanding and performance, ultimately fostering a more effective and inclusive learning environment.